The lost Politburo transcripts : from collective rule to Stalin's dictatorship - Gregory, Paul R.; Naimark, Norman M. (Yale-Hoover series on Stalin, Stalinism, and the Cold War., 2008)
Prominent Westen and Russian scholars examine the 'lost' transcripts of the Soviet Politburo, a set of verbatim accounts of meetings that took place from the 1920s to 1938 but remained hidden in secret archives until the late 1990s.